Pet-friendly Policy in Upscale and Luxury Tourism Accommodations: Service Customizations Under SERVQUAL - Kongtaveesawas, Natnisha; Namwong, Suwaree (Dusit Thani College Journal, 2020)
The trend of people traveling with their pets has become an emerging market in tourism and hospitality business. In upscale hotels, customization strategies according to various segments of customers have become competitive advantages. According to the expanding of pet related market, setting the boundaries of services through pet policy to cater pet owners and non-pet owners while maintaining the luxury image could be crucial for the management. The detailed studies of consumer’s behaviors and SERVQUAL as the service measurement are the major area of this academic paper. This article is divided into four major parts. Part one describes the overview of pet-owning consumer behavior, including the growth rate and constraint of pet-friendly policy in tourism and hospitality accommodation segment, objectives, scope of research, and definition of operational terms are also mentioned. Part two is the literature review of SERVQUAL together with pet policies as service customization strategies in hotel management responding to pet related consumers behavior. Part three is the conclusion of the paper and part four is the implications and discussion for the further research.